THE CHARACTERISTICS OF TURKISH FOREIGN TRADE COMPANIES: A Field Study - Mustafa Abdül Metin Dinçer; Tuğba Onur; Esra Dil (İşletme Bilimi Dergisi)
Aim: This study aims to reveal the characteristics of Turkish foreign trade companies.Method: This research is a qualitative study which reveals the qualifications of these companies by focusing on the types of foreign trade firms (as actors), what kind of sector structure they are operating in (ecosystem) and their growth trends. The characteristics of the 79 firms obtained from content analysis of the semi-structured interviews.Findings: Findings show that companies are mostly concentrated in the Marmara Region, they legally have corporation status, employ 200 or more employees and they operate in the manufacturing sector. They both import and export, and tend to enter all markets without preference of a specific region.